Efficient DAG Task Scheduling Algorithm for Wireless Sensor Networks - Kaur, Mandeep; Sohi, Balwinder Singh (International Journal of Computer Sciences and Engineering, 2018)
WSN (Wireless Sensor Network) has to be systemized to being resource effective and extensible. The concept of task scheduling requires less task completion time, less energy consumption and proper utilization of energy with fewer energy nodes. DAG (Directed Acyclic Graph) is considered for WSN organization as of the routing redundancy for the root. This research paper has aimed to enhance the performance of DAG in WSN. For the improvement, Cuckoo Search as an optimization algorithm and Support Vector Machine as a classification algorithm is utilized. For the evaluation of the proposed work, QoS parameters, such as Throughput, PDR (Packet Delivery Ratio), Energy Consumption, Network Lifetime and Delay are considered. The proposed algorithm stood very positive results for each QoS parameter. The results are compared on the base of with and without the proposed architecture.